Need Assessment Analysis on Android Based Interactive Multimedia Application in High School Geography Learning - Wijaya, Nyokro Mukti; Herlina, Meri; M, Indah Fitria (Journal Learning Geography, 2024)
This study aims to 1) Know the ICT-based geography learning media currently used, (2) to know teachers’ and students’ need for Android-based geography interactive multimedia, and (3) determine the appropriate type of interactive multimedia to be developed. The type of research is qualitative research with a questionnaire as the instrument. Qualitative data was used to answer research objectives. Respondents in this study were geography teachers and students of class XI IPS of Public Senior High School 12 Pekanbaru. The results showed that; (1) the type of ICT-based learning media used in geography learning is still dominated by the use of PowerPoint slides, instructional videos, and the internet, (2) teachers and students desperately need interactive multimedia on Android-based geography to help the learning process of geography be more interesting and interactive. (3) Types of interactive multimedia based on android that can be developed are drill and practice, tutorials, simulations, and games. This research suggested developing interactive multimedia based on android geography as well as training for geography teachers to produce their own.Keyword: need assessment; interactive multimedia; geography learning